2023
DOI: 10.2196/38732
|View full text |Cite
|
Sign up to set email alerts
|

The Vaping and Patterns of e-Cigarette Use Research Study: Protocol for a Web-Based Cohort Study

Abstract: Background In total, 3.2% of American adults report using e-cigarettes every day or some days. The Vaping and Patterns of E-cigarette Use Research (VAPER) Study is a web-based longitudinal survey designed to observe patterns in device and liquid use that suggest the benefits and unintended consequences of potential e-cigarette regulations. The heterogeneity of the e-cigarette devices and liquids on the market, the customizability of the devices and liquids, and the lack of standardized reporting re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…The sample was generally similar to that of the nationally representative 2019 Tobacco Use Supplement to the Current Population Survey (TUS-CPS) in sociodemographic information; ( Hardesty et al, 2023 ) however, post-stratification survey weights for gender/age/race were developed and implemented based on data from the 2019 TUS-CPS to ensure our sample was representative of U.S. adult frequent ENDS users.…”
Section: Methodsmentioning
confidence: 99%
“…The sample was generally similar to that of the nationally representative 2019 Tobacco Use Supplement to the Current Population Survey (TUS-CPS) in sociodemographic information; ( Hardesty et al, 2023 ) however, post-stratification survey weights for gender/age/race were developed and implemented based on data from the 2019 TUS-CPS to ensure our sample was representative of U.S. adult frequent ENDS users.…”
Section: Methodsmentioning
confidence: 99%
“…The substantial sample size of this study is one strength of these analyses. Additionally, the VAPER sample closely resembles the national sample of adults who use ENDS daily, captured by the 2019 TUS-CPS 11 . The data reported here were captured directly from participant photos of their devices and liquids and from manufacturer, academic, retail, and review sites; therefore, these data are only as accurate as the photos and sites utilized for coding.…”
Section: Discussionmentioning
confidence: 99%
“…Rigorous data review and cleaning procedures were employed to ensure high quality data. Additional information about study protocols, including data review, is available elsewhere 11 ; of note, the VAPER sample is similar to the nationally representative sample of adults frequently using ENDS in the 2019 Tobacco Use Supplement to the Current Population Survey (TUS-CPS) in regard to gender, race, age, and region, though the VAPER sample includes a larger proportion of lower income individuals 11 .…”
Section: Methodsmentioning
confidence: 99%
“…This study used wave 5 (February-April 2023) data (n = 1290) of the Vaping and Patterns of E-cigarette Use Research (VAPER) study, a longitudinal cohort study among U.S. adults (age 21 + ) using ENDS at least 5 days/week. Details about the VAPER Study methodology have been reported ( Hardesty et al, 2023 ). Adults were recruited to participate in an online survey hosted by REDCap and were asked to report their ENDS use behaviors.…”
Section: Methodsmentioning
confidence: 99%